2D AlN crystal phase formation on (0001) Al2O3 surface by ammonia MBE. Issue 4 (18th March 2015) - Malin, Timur; Mansurov, Vladimir; Galitsyn, Yury; Zhuravlev, Konstantin
Abstract: Kinetics of a two‐dimensional (2D) AlN layer formation on (0001) sapphire (Al2 O3 ) surface during nitridation at different ammonia fluxes is investigated by reflection high energy electron diffraction (RHEED). The process on the surface is described in the framework of a chemical reactions kinetic model including interaction between partially reduced aluminum oxide species (AlO) and chemisorbed NH2 particles. The experimentally determined AlN formation rates as functions of both the temperature and the ammonia pressure are successfully described by a simple set of kinetic equations. Calculated maximum rate of the process well agrees with the experimental values. Precision measurement of 2D AlN lattice parameters during the nitridation process detects the value of 3.01 Å. This value coincides exactly with a characteristic structure parameter of the oxygen‐deficient Al2 O3 surface. We assume this coincidence results from flexibility of the 2D AlN monolayer which provides minimization of elastic stresses at the AlN/(0001)Al2 O3 interface. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)